Malignant pleural mesothelioma with resolution of pleural effusion - Sayaka Nishida; Kazutoshi Toriyama; Makiko Yomota; Yukio Hosomi (Respirology Case Reports, 2023)
Key message In malignant pleural mesothelioma patients, pleural effusion may improve during the course of the disease. Pleural effusion with nodular shadows bordering the pleura should be followed up even if the pleural effusion improves.